A Tale of Two Duchies: An Architectural Primer - Bob Burnham; William C. Miller (Oz, 1983)
"A Tale of Two Duchies" is a series of four short episodic problems given in the Architectural Design Studio (ADS 1) course during the 1982 fall semester at Kansas State University…